PENGARUH INFUSIA KULIT BUAH MANGGIS (Garcinia mangostana L.) TERHADAP JUMLAH SEL RADANG DI FARING PADA TIKUS PUTIH (Rattus norvegicus) YANG DIINDUKSI ASAP ROKOK - Punomo, Yuli; Hartadiyati, Eny (BIOMA, 2015)
This reserach aimed to analyze the effect of mangosteen peel infusionin flammatory cells on mice pharynx. The design used RandomizedControl Design Post Test. It analyzed with Kruskal-Wallis nonparametric95%. The results showed inflammatory cells was 157.7 ±10.41 for control (P0), 337.5 ± 18.48 for treatments P1, 287.5 ± 11.90to 247.5 ± treatments P2 and P3 19.36 for treatment. The conclusionfor this research was infusion mangosteen peel significantly affectedon the number of inflammatory cells (p<0.05).Keywords: inflammatory cells, infusia mangosteen rind(Garcinia mangostana L), pharynx